Demonstration that the Group II Intron from the Clostridial Conjugative Transposon Tn5397 Undergoes Splicing In Vivo - Roberts, Adam P. (American Society for Microbiology, 2001)
Previous work has identified the conjugative transposon Tn5397 from Clostridium difficile. This element was shown to contain a group II intron. Tn5397 can be conjugatively transferred from C. difficile to Bacillus subtilis. In this work we show that the intron is spliced in both these hosts and that nonspliced RNA is also present. We constructed a mutation in the open reading frame within the intron, and this prevented splicing but did not prevent the formation of the circular form of the conjugative transposon (the likely transposition intermediate) or decrease the frequency of intergeneric transfer of Tn5397. Therefore, the intron is spliced, but splicing is not required for conjugation of Tn5397.